Laminate and packaging material
Through the combination of the multi-layer polyethylene film structure and the inorganic oxide layer, the wrinkles and heat resistance problems of packaging materials during the single materialization process are solved, and the stability of gas barrier properties and the feasibility of recycling are achieved.
Patent Information
- Application Number
- JP2023122188
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-27
- Publication Date
- 2025-02-06
AI Technical Summary
In the process of achieving single materialization and recycling, existing packaging materials are prone to surface wrinkles and difficult to maintain gas barrier properties and heat resistance, especially during heating and disinfection.
A multi-layer polyethylene film structure is adopted, including a surface layer, an intermediate layer and a back layer. Each layer is composed of polyethylene resins of different density and melting points, and combined with an inorganic oxide layer and a gas barrier coating to ensure interlayer adhesion and heat resistance.
It can maintain excellent gas barrier properties and adhesion after heating and disinfection, and improve the recycling rate and processing stability of packaging materials.
Smart Images

Figure 2025018467000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate and a packaging material. [Background technology]
[0002] Packaging materials used for packaging foods, medicines, etc. are required to have the property of preventing the intrusion of gases (water vapor, oxygen, etc.) that denature the contents (gas barrier properties) in order to prevent deterioration or spoilage of the contents and maintain their function and quality. In addition, packaging materials are required to have excellent heat resistance because they may be subjected to heat sterilization treatment such as boiling. For this reason, laminates having gas barrier properties and heat resistance are used for these packaging materials.
[0003] As such a laminate, one in which a gas barrier layer made of a material having gas barrier properties is provided on the surface of a resin substrate is known. As the gas barrier layer, metal foil, metal vapor deposition film, coating film formed by a wet coating method, etc. are known. As the resin substrate, a polyolefin film such as a polyethylene film is known. For example, Patent Document 1 describes an aluminum vapor deposition polyethylene film characterized by having an aluminum vapor deposition film on the surface of a non-oriented polyethylene film having a thickness of less than 30 μm and made of linear low-density polyethylene produced by using a metallocene catalyst.
[0004] Also, it has been considered to improve the properties of the laminate by using a substrate having a plurality of resin layers as the substrate. For example, Patent Document 2 describes a film capable of suppressing the occurrence of wrinkles, which comprises a resin layer including a first surface and a second surface, and a deposition layer provided on the second surface of the resin layer, and the resin layer has a density higher than that of the first layer constituting the first surface, and a density of 0.934 g / cm3. 3 and at least one hard layer having a density of at least 1000 nm, wherein the total thickness of the hard layers is at least 60% of the total thickness of the resin layer. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2001-179878 A [Patent Document 2] JP 2018-24213 A Summary of the Invention [Problem to be solved by the invention]
[0006] In recent years, due to growing environmental awareness triggered by the problem of marine plastic waste, there is a demand for more efficient sorting and recovery of plastic materials and recycling, and there is also a demand for mono-material packaging materials.
[0007] However, in conducting research to develop a mono-material laminate, the inventors found that, depending on the type of polyethylene resin that constitutes each layer of the polyethylene film, wrinkles may occur on the surface of the polyethylene film, making it difficult to form a gas barrier layer or to impart sufficient heat resistance.
[0008] Therefore, one aspect of the present invention aims to provide a laminate that has excellent recyclability, excellent processing stability when providing a gas barrier layer, excellent heat resistance that allows the gas barrier property to be maintained even after heat sterilization treatment, and adhesion to a heat seal layer. [Means for solving the problem]
[0009] One aspect of the present invention includes the following [1] to [8]. [1] A laminate comprising a multilayer polyethylene film, an inorganic oxide layer, an adhesive layer, and a sealant layer, The multilayer polyethylene film has at least three layers, a surface layer, an intermediate layer, and a back layer, in this order on the sealant layer side; the probe drop temperature of the intermediate layer is higher than the probe drop temperature of the surface layer and is equal to or higher than the probe drop temperature of the back layer; The surface layer has a thickness of 0.926 g / cm 3 It is made of medium density polyethylene resin or high density polyethylene resin having a density of or above, A laminate, wherein the content of the polyethylene resin in the laminate is 90 mass% or more based on the total amount of the laminate. [2] The density of the multilayer polyethylene film is 0.942 g / cm 3 The laminate described in [1] above. [3] The laminate according to [1] or [2], wherein the intermediate layer has a probe drop temperature of 125°C or higher. [4] The laminate according to any one of [1] to [3], wherein the thickness of the intermediate layer is 33% or more of the thickness of the multilayer polyethylene film. [5] The laminate according to any one of [1] to [4], wherein the absolute value of the degree of molecular orientation of the multilayer polyethylene film is less than 1.07. [6] The laminate according to any one of [1] to [5], further comprising a gas barrier coating layer disposed on the surface of the inorganic oxide layer on the heat seal side. [7] The laminate according to any one of [1] to [6], wherein the adhesive layer contains a gas barrier adhesive. [8] A second adhesive layer disposed on the back layer side surface of the multilayer polyethylene film; The laminate according to any one of [1] to [7], further comprising a substrate disposed via the second adhesive layer. [9] A packaging material comprising the laminate according to any one of [1] to [8]. Effect of the Invention
[0010] According to one aspect of the present invention, it is possible to provide a laminate having excellent recyclability, excellent processing stability when providing a gas barrier layer, excellent heat resistance that allows the gas barrier property to be maintained even after heat sterilization treatment, and adhesion to a heat seal layer. [Brief description of the drawings]
[0011] [Figure 1]FIG. 1 is a cross-sectional view of a laminate according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of a laminate according to another embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view of a laminate according to another embodiment of the present invention. [Figure 4] FIG. 4 is a cross-sectional view of a laminate according to another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, the embodiments of the present disclosure will be described in detail with reference to the drawings. Note that the drawings are schematic, and for example, the relationship between thickness and planar dimensions, and the ratio of thicknesses of each layer are different from the actual ones. In addition, the embodiments shown below are examples of configurations for embodying the technical idea of the present disclosure, and the technical idea of the present disclosure is not limited to the materials, shapes, structures, etc. of the components described below.
[0013] [Laminate] 1 is a cross-sectional view of a laminate according to one embodiment of the present invention. The laminate 100 includes a multilayer polyethylene film 10, an inorganic oxide layer 21, a gas barrier coating layer 22, an adhesive layer 30, and a sealant layer 40.
[0014] The content of the polyethylene resin in the laminate 100 may be 90% by mass or more, or 95% by mass or more, based on the total amount of the laminate 100, from the viewpoint of realizing mono-materialization and excellent recyclability.
[0015] The thickness of the laminate 100 is not particularly limited and can be appropriately determined depending on the cost and the application. The thickness of the laminate 100 may be 50 μm or more, 60 μm or more, or 70 μm or more, and may be 300 μm or less, 250 μm or less, or 200 μm or less.
[0016] <Multi-layer polyethylene film> The multilayer polyethylene film 10 includes three layers, a surface layer 11, an intermediate layer 12, and a back layer 13, in this order on the sealant layer 40 side. The surface layer 11 and the back layer 13 are each the outermost layer of the multilayer polyethylene film 10.
[0017] The content of polyethylene resin in the multilayer polyethylene film 10 may be 90 mass % or more, or 95 mass % or more, based on the total amount of the multilayer polyethylene film 10, from the viewpoint of realizing mono-materialization and excellent recyclability.
[0018] The density of the multilayer polyethylene film 10 may be in the following range from the viewpoints of wrinkle resistance, excellent processing stability, and heat resistance that can maintain gas barrier properties even after heat sterilization treatment. The density of the multilayer polyethylene film 10 is 0.935 g / cm 3 More than 0.940g / cm 3 More than 0.945g / cm 3 More than 0.950g / cm 3 or more than 0.955g / cm 3 The density of the multilayer polyethylene film 10 may be 0.980 g / cm or more. 3 Below, 0.975g / cm 3 Below, 0.970g / cm 3 Below, 0.965g / cm 3 or less than 0.960g / cm 3 It may be the following.
[0019] The multilayer polyethylene film 10 may be an unstretched film. The multilayer polyethylene film 10 being unstretched means that the absolute value of the molecular orientation degree of the multilayer polyethylene film is less than 1.07. When the multilayer polyethylene film 10 is unstretched (the absolute value of the molecular orientation degree is less than 1.07), the gas barrier layer 20 is less likely to peel off in the vicinity of the surface layer 11 of the multilayer polyethylene film 10, and the adhesion to the gas barrier layer 20 is excellent. The absolute value of the molecular orientation degree means a value measured by the method described in the Examples below.
[0020] The thickness of the multilayer polyethylene film 10 is not particularly limited and can be appropriately determined according to the cost and application, taking into consideration the suitability as a packaging material and the suitability for lamination with other layers. The thickness of the multilayer polyethylene film 10 may be 3 μm or more, 5 μm or more, 6 μm or more, or 10 μm or more, or may be 200 μm or less, 120 μm or less, 100 μm or less, or 40 μm or less.
[0021] (surface) The surface layer 11 is 0.926 g / cm 3 The surface layer 11 is a layer made of a medium density polyethylene resin or a high density polyethylene resin having a density of 0.926 g / cm 3 By being composed of the above medium density polyethylene resin or high density polyethylene resin, the laminate 100 has excellent heat resistance. In this specification, high density polyethylene resin means a polyethylene resin having a density of 0.942 g / cm 3 Hereinafter, the polyethylene resin constituting the surface layer 11 will also be referred to as a first polyethylene resin.
[0022] The content of the first polyethylene resin in surface layer 11 may be 90 mass% or more, 95 mass% or more, or 98 mass% or more, or may be 100 mass% (an embodiment in which surface layer 11 is substantially composed of the first polyethylene resin) based on the total amount of surface layer 11. When surface layer 11 is composed of multiple polyethylene resins (for example, multiple polyethylene resins having different average molecular weights, densities, etc.), a mixture of the multiple polyethylene resins is used as the first polyethylene resin.
[0023] From the viewpoints of being less prone to wrinkles, having better processing stability, and having better heat resistance and therefore being able to easily maintain gas barrier properties even after heat sterilization, the surface layer 11 may be made of a first polyethylene resin having a density in the following range. The density of the first polyethylene resin is 0.930 g / cm. 3 More than 0.935g / cm 3 or more than 0.940g / cm 3 The density of the first polyethylene resin may be 0.970 g / cm or more.3 Below, 0.965g / cm 3 or less than 0.960g / cm 3 The density of the first polyethylene resin may be 0.960 g / cm or less. 3 By satisfying the above condition, the surface of the multilayer polyethylene film 10 can be prevented from becoming rough and resin powder can be prevented from being generated, making it easier to achieve excellent gas barrier properties.
[0024] The melt flow rate MFR1 of the first polyethylene resin at 190°C and a load of 2.16 kg is not particularly limited and can be appropriately adjusted depending on the method for producing the first polyethylene resin. The melt flow rate MFR1 of the first polyethylene resin at 190°C and a load of 2.16 kg may be 5 g / 10 min or less, 3 g / 10 min or less, or 1.5 g / 10 min or less. The MFR1 of the first polyethylene resin may be 0.1 g / 10 min or more, or 0.3 g / 10 min or more. In this specification, the melt flow rate means a value measured in accordance with JIS K6921-2.
[0025] The probe drop temperature of the surface layer 11 may be 120°C or more, 125°C or more, 130°C or more, or 133°C or more from the viewpoint of wrinkles being less likely to occur and processing stability being more excellent, and from the viewpoint of heat resistance being more excellent and gas barrier properties being more easily maintained even after heat sterilization treatment. The probe drop temperature of the surface layer 11 may be 160°C or less, 155°C or less, 150°C or less, or 146°C or less. By having the probe drop temperature of the surface layer 11 be 150°C or less, it is possible to suppress the surface of the multilayer polyethylene film 10 from becoming rough and the generation of resin powder, and it is easy to realize excellent gas barrier properties. In this specification, the probe drop temperature means a value measured by the method described in the Examples below.
[0026] The probe drop temperature is a parameter related to the local thermal analysis of a material using a probe, and can be obtained by measuring the rising and falling behavior of the probe. To measure the probe drop temperature, an atomic force microscope (AFM) equipped with a cantilever (probe) with a heating mechanism and a nanothermal microscope is used. When the cantilever is brought into contact with the surface of a solid sample fixed to a sample stage and a voltage is applied to the cantilever in contact mode to heat it, the sample surface thermally expands and the cantilever rises. When the cantilever is further heated, the sample surface softens and its hardness changes significantly. As a result, the cantilever descends and penetrates into the sample surface. The starting point of the sudden displacement detected at this time is the probe drop starting point, and the probe drop temperature can be obtained by converting the voltage into temperature. By this method, the probe drop temperature can be known locally in the nanoscale region and near the surface.
[0027] Examples of AFMs that can be used include the MPF-3D-SA and Ztherm systems manufactured by Oxford Instruments, and the Nano Thermal Analysis series and nanoIR series manufactured by Bruker Japan. Measurements can also be performed with AFMs manufactured by other manufacturers by attaching the Nano Thermal Analysis. Examples of cantilevers that can be used include the AN2-200 manufactured by Anasys Instruments. Cantilevers other than those listed above can be used as long as they can sufficiently reflect laser light and can be applied with voltage.
[0028] The temperature range in the measurement of the probe drop temperature varies depending on the material to be measured, but for example, the start temperature can be about room temperature, 25° C., and the end temperature can be about 400° C. In this specification, the temperature range in the measurement of the probe drop temperature can be from 25° C. to 300° C.
[0029] The spring constant of the cantilever may be 0.1 to 3.5 N / m, and is preferably 0.5 to 3.5 N / m in order to perform measurements in both tapping and contact modes. In AFM, the deflection of the cantilever may be detected in units of voltage. In contact mode, the deflection of the cantilever changes before and after contact between the cantilever and the sample. By keeping this change within the range of 0.1 to 3.0 V, it is possible to prevent damage to the sample surface while keeping the cantilever in contact with the sample.
[0030] The temperature rise rate of the cantilever varies depending on the heating mechanism, etc., but may be 0.1 to 10 V / sec, and is preferably 0.2 to 5 V / sec. When the sample surface softens, the tip of the cantilever penetrates into the sample and descends. The amount of penetration of the cantilever affects the detection sensitivity of the peak top of the softening curve, and can be 3 to 500 nm. From the viewpoint of preventing damage to the cantilever, it is more preferable to set the amount of penetration to 5 to 100 nm.
[0031] In order to calculate the probe drop temperature, it is necessary to create a calibration curve. In the examples described later, polycaprolactone, low-density polyethylene, polypropylene, and polyethylene terephthalate were used as calibration samples. Details of the creation of the calibration curve will be described later. The material of the calibration sample is not limited to the above, and at least one of the following may be used: a material whose thermal conductivity is not significantly different from that of a general polymer, and whose melting point is near 60°C, near 250°C, and between them. For example, it is also possible to use only three of the above four calibration samples, excluding polypropylene: polycaprolactone, low-density polyethylene, and polyethylene terephthalate. In order to measure the sample temperature accurately, a calibration curve was created after the sample was measured. Four types of calibration samples were used: polycaprolactone (melting point: 55°C), low-density polyethylene (LDPE, melting point: 110°C), polypropylene (PP, melting point: 164°C), and polyethylene terephthalate (PET, melting point: 235°C). Each was measured twice at different measurement positions, and a calibration curve was created using the average value as the probe drop temperature. Using this calibration curve, the voltage was set as the probe drop start point, and the temperature was converted to the probe drop temperature.
[0032] The thickness of the surface layer 11 is not particularly limited, and can be appropriately determined according to the cost and the application, taking into consideration the suitability of the manufacturing method and the apparatus, and the suitability for lamination with other layers. From a practical viewpoint, the thickness of the surface layer 11 may be 1 μm or more, 2 μm or more, 3 μm or more, 4 μm or more, or 5 μm or more, or may be 50 μm or less, 30 μm or less, 20 μm or less, or 10 μm or less.
[0033] (Middle class) The intermediate layer 12 is a layer containing a polyethylene resin. Hereinafter, the polyethylene resin constituting the intermediate layer 12 is also referred to as a second polyethylene resin. The content of the second polyethylene resin in the intermediate layer 12 may be 90% by mass or more, 95% by mass or more, or 98% by mass or more based on the total amount of the intermediate layer 12, or may be 100% by mass (an embodiment in which the intermediate layer 12 is substantially composed of the second polyethylene resin). When the intermediate layer 12 is composed of a plurality of polyethylene resins (e.g., a plurality of polyethylene resins having different average molecular weights, densities, etc.), a mixture of the plurality of polyethylene resins is defined as the second polyethylene resin.
[0034] From the viewpoints of being less prone to wrinkles, having better processing stability, and having better heat resistance and therefore being able to easily maintain gas barrier properties even after heat sterilization treatment, the intermediate layer 12 may be made of a second polyethylene resin having a density in the following range. The density of the second polyethylene resin is 0.940 g / cm 3 More than 0.945g / cm 3 or more than 0.950g / cm3 The density of the second polyethylene resin may be 0.980 g / cm or more. 3 Below, 0.975g / cm 3 Below, 0.970g / cm 3 or less than 0.965g / cm 3 It may be the following.
[0035] The melt flow rate MFR2 of the second polyethylene resin at 190°C under a load of 2.16 kg is not particularly limited and can be appropriately adjusted depending on the method for producing the second polyethylene resin. The melt flow rate MFR2 of the second polyethylene resin at 190°C under a load of 2.16 kg may be 5 g / 10 min or less, 3 g / 10 min or less, 2 g / 10 min or less, or 1.5 g / 10 min or less. The MFR2 of the second polyethylene resin may be 0.1 g / 10 min or more, 0.5 g / 10 min or more, or 0.8 g / 10 min or more.
[0036] The higher the probe drop temperature of the intermediate layer 12, the easier it is to achieve excellent heat resistance. The probe drop temperature of the intermediate layer 12 may be 125°C or higher, 130°C or higher, 135°C or higher, 138°C or higher, 140°C or higher, or 142°C or higher, from the viewpoint of wrinkles being less likely to occur and processing stability being more excellent, and from the viewpoint of heat resistance being more excellent and gas barrier properties being more easily maintained even after heat sterilization treatment. The probe drop temperature of the intermediate layer 12 may be 170°C or lower, 165°C or lower, 160°C or lower, 157°C or lower, or 155°C or lower.
[0037] The probe drop temperature of the intermediate layer 12 is higher than the probe drop temperature of the surface layer 11 and equal to or higher than the probe drop temperature of the back layer 13. By having the probe drop temperature of the intermediate layer 12 higher than the probe drop temperature of the surface layer 11 and equal to or higher than the probe drop temperature of the back layer 13, wrinkles are less likely to occur, excellent heat resistance can be achieved, and gas barrier properties can be maintained even after heat sterilization treatment.
[0038] From the viewpoints of preventing wrinkles more easily and improving processing stability, and of improving heat resistance and making it easier to maintain gas barrier properties even after heat sterilization treatment, the difference between the probe drop temperature of the intermediate layer 12 and the probe drop temperature of the surface layer 11 and / or the back layer 13 may be 3° C. or more, 5° C. or more, or 8° C. or more. The difference between the probe drop temperature of the intermediate layer 12 and the probe drop temperature of the surface layer 11 and / or the back layer 13 may be 20° C. or less, 15° C. or less, or 13° C. or less.
[0039] The thickness of the intermediate layer 12 is not particularly limited, and can be appropriately determined according to the cost and application, taking into consideration the suitability of the manufacturing method and device, and the suitability for lamination with other layers. From a practical standpoint, the thickness of the intermediate layer 12 may be 5 μm or more, 8 μm or more, 10 μm or more, 12 μm or more, or 15 μm or more, or may be 80 μm or less, 50 μm or less, 40 μm or less, or 30 μm or less.
[0040] The greater the thickness of the intermediate layer 12, the better the heat resistance that can be achieved. From the viewpoint of having better heat resistance and being able to easily maintain the gas barrier property even after heat sterilization treatment, the thickness of the intermediate layer 12 may be 30% or more, 33% or more, 40% or more, 50% or more, 55% or more, or 60% or more of the thickness of the multilayer polyethylene film 10. The thickness of the intermediate layer 12 may be 80% or less, 77% or less, or 75% or less of the thickness of the multilayer polyethylene film 10.
[0041] The thickness of the intermediate layer 12 may be greater than the thickness of the surface layer 11 and / or the thickness of the back layer 13 from the viewpoint of being more heat resistant and easily maintaining the gas barrier property even after heat sterilization. The thickness of the intermediate layer 12 may be 1 or more times, 1.5 or more times, 2 or more times, 2.5 or more times, or 3 or more times the thickness of the surface layer 11 and / or the back layer 13 from the viewpoint of being more heat resistant and easily maintaining the gas barrier property even after heat sterilization. The thickness of the intermediate layer 12 may be 8 or less times, 7 or less times, 6.5 or less times, or 6 or less times the thickness of the surface layer 11 and / or the back layer 13.
[0042] (Back layer) The back layer 13 is a layer containing a polyethylene resin. Hereinafter, the polyethylene resin constituting the back layer 13 is also referred to as a third polyethylene resin. The content of the third polyethylene resin in the back layer 13 may be 90% by mass or more, 95% by mass or more, or 98% by mass or more based on the total amount of the back layer 13, or may be 100% by mass (an embodiment in which the back layer 13 is substantially composed of the third polyethylene resin). When the back layer 13 is composed of multiple polyethylene resins (e.g., multiple polyethylene resins having different average molecular weights, densities, etc.), a mixture of the multiple polyethylene resins is referred to as the third polyethylene resin.
[0043] The back layer 13 may be made of a third polyethylene resin having a density in the following range from the viewpoints of wrinkle resistance, better processing stability, and better heat resistance and easier maintenance of gas barrier properties even after heat sterilization treatment. The density of the third polyethylene resin is 0.920 g / cm 3 More than 0.926g / cm 3 More than 0.930g / cm 3 More than 0.935g / cm 3 or more than 0.940g / cm 3 The third polyethylene resin may have a density of 0.970 g / cm or more. 3 Below, 0.965g / cm 3 or less than 0.960g / cm 3 The third polyethylene resin may have a density of 0.960 g / cm or less. 3 The above-mentioned conditions can suppress the surface of the multilayer polyethylene film 10 from becoming rough and the generation of resin powder. By suppressing the generation of resin powder, adhesion of resin powder to the surface of the front layer 11 side of the multilayer polyethylene film 10 when the multilayer polyethylene film 10 is wound into a roll can be suppressed, making it easier to achieve excellent gas barrier properties.
[0044] The probe drop temperature of the back layer 13 may be 120°C or more, 125°C or more, 130°C or more, or 133°C or more from the viewpoint of wrinkles being less likely to occur and processing stability being more excellent, and from the viewpoint of heat resistance being more excellent and gas barrier properties being more easily maintained even after heat sterilization treatment. The probe drop temperature of the back layer 13 may be 160°C or less, 155°C or less, 150°C or less, or 146°C or less. By having the probe drop temperature of the back layer 13 be 160°C or less, it is possible to suppress the surface of the multilayer polyethylene film 10 from becoming rough and the generation of resin powder. By suppressing the generation of resin powder, it is possible to suppress the adhesion of resin powder to the surface of the front layer 11 side of the multilayer polyethylene film 10 when the multilayer polyethylene film 10 is wound into a roll, and it is easy to realize excellent gas barrier properties.
[0045] The thickness of the back layer 13 is not particularly limited, and can be appropriately determined according to the cost and application, taking into consideration the suitability of the manufacturing method and device, and the suitability for lamination with other layers. From a practical standpoint, the thickness of the back layer 13 may be 1 μm or more, 2 μm or more, 3 μm or more, 4 μm or more, or 5 μm or more, or 50 μm or less, 30 μm or less, 20 μm or less, or 10 μm or less.
[0046] The back layer 13 may have the same configuration as the front layer 11. That is, the multilayer polyethylene film 10 may have a symmetrical structure with respect to the intermediate layer 12. When the multilayer polyethylene film 10 has a symmetrical structure, curling during production of the multilayer polyethylene film 10 can be suppressed, and the multilayer polyethylene film 10 can be produced stably.
[0047] The surface layer 11, the intermediate layer 12, and the back layer 13 may contain a resin other than polyethylene resin as appropriate, as long as the recyclability is not impaired. Examples of such resins include ethylene-vinyl acetate copolymer (EVA), ethylene-α-olefin copolymer, ethylene-(meth)acrylic acid copolymer, homopolypropylene resin (PP), propylene-ethylene random copolymer, propylene-ethylene block copolymer, propylene-α-olefin copolymer, olefin resins such as polybutene, polyamide, polyethylene vinyl alcohol, polyester, various modifying resins, etc. In addition, each of them may independently contain one or more additives. Examples of additives include crosslinking agents, antioxidants, antiblocking agents, lubricants (slip agents), ultraviolet absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, and pigments.
[0048] The intermediate layer 12 may be a single layer or may be formed of multiple layers. For example, as shown in Fig. 2, the multilayer polyethylene film 50 in the laminate 200 has a surface layer 51, an intermediate layer 52, and a back layer 53, and the intermediate layer 52 has resin layers 52a, 52b, and 52c. In this case, the resin layers 52a, 52b, and 52c all have the same composition. The fact that the intermediate layer 52 has multiple layers can be confirmed by observing the cross section of the multilayer polyethylene film 50 with an electron microscope or an optical microscope.
[0049] The multilayer polyethylene film 10 may have layers other than the three layers of the surface layer 11, the intermediate layer 12, and the back layer 13. For example, as shown in FIG. 3, the multilayer polyethylene film 60 in the laminate 300 has a surface layer 61, an intermediate layer 62, and a back layer 63, a resin layer 64 between the surface layer 61 and the intermediate layer 62, and a resin layer 65 between the intermediate layer 62 and the back layer 63. The resin layer 64 is, for example, a layer containing a polyethylene resin and having a different composition from the surface layer 61 and the intermediate layer 62. The resin layer 65 is, for example, a layer containing a polyethylene resin and having a different composition from the intermediate layer 62 and the back layer 63. The multilayer polyethylene film may have, for example, three layers, five layers, seven layers, or more layers. may be, for example, 3 layers, 5 layers, 7 layers, or more.
[0050] Each layer of the multilayer polyethylene film 10 may be made of a polyethylene resin having a density in the following ranges, from the viewpoints of being less prone to wrinkles, having better processing stability, and having better heat resistance and therefore being able to easily maintain gas barrier properties even after heat sterilization treatment. The density of the polyethylene resin is 0.930 g / cm 3 More than 0.940g / cm 3 More than 0.945g / cm 3 or more than 0.950g / cm 3 The density of the polyethylene resin is 0.980 g / cm or more. 3 Below, 0.975g / cm 3 Below, 0.970g / cm 3 or less than 0.965g / cm 3 It may be the following.
[0051] The method for producing the multilayer polyethylene film 10 is not particularly limited, and the multilayer polyethylene film 10 can be produced by a known method such as an air-cooled inflation method, a water-cooled inflation method, or a T-die casting method. From the viewpoint of versatility, the multilayer polyethylene film 10 may be produced by an inflation method or an air-cooled inflation method. The air-cooled inflation method is a method in which a die having an annular lip called a ring die (or a crosshead die) is installed at the tip of an extruder, and a material is extruded into a tube shape and continuously molded. More specifically, an air hole is installed in the center of the ring die, and compressed air is blown in from the air hole to expand the tube, and the multilayer polyethylene film 10 can be produced by cooling the tube while pulling it with a roller called a pinch roll and winding up the film.
[0052] The obtained multilayer polyethylene film 10 may be subjected to a surface modification treatment to improve suitability for subsequent processes, if necessary. For example, the surface of the multilayer polyethylene film 10 may be modified to improve printability or lamination suitability during lamination. Examples of the modification treatment include treatments that generate functional groups by oxidizing the film surface, such as corona discharge treatment, plasma treatment, and flame treatment, and modification treatments by a wet process that forms an easy-adhesion layer by coating.
[0053] <Gas barrier layer> The gas barrier layer 20 is a layer provided on the multilayer polyethylene film 10 from the viewpoint of improving the gas barrier property against water vapor and oxygen. The gas barrier layer 20 is preferably a layer having transparency. The gas barrier layer 20 has an inorganic oxide layer 21 and a gas barrier coating layer 22. The gas barrier layer 20 may have both the inorganic oxide layer 21 and the gas barrier coating layer 22, or may have only the inorganic oxide layer 21.
[0054] (Inorganic oxide layer) The inorganic oxide layer 21 contains an inorganic oxide. Examples of inorganic oxides include aluminum oxide, silicon oxide, tin oxide, magnesium oxide, and mixtures thereof. From the viewpoint of more easily maintaining gas barrier properties and adhesion even after heat sterilization treatment, more excellent heat resistance, and transparency, the inorganic oxide layer 21 may contain at least one selected from the group consisting of aluminum oxide, silicon oxide, and magnesium oxide.
[0055] The thickness of the inorganic oxide layer 21 may be 5 to 150 nm. If the thickness of the inorganic oxide layer 21 is 5 nm or more, it is easy to form a layer having a uniform and sufficient film thickness, and sufficient gas barrier properties can be realized. If the thickness of the inorganic oxide layer 21 is 150 nm or less, flexibility can be imparted to the inorganic oxide layer 21, and even if an external load such as bending or pulling is applied after the inorganic oxide layer 21 is formed, the inorganic oxide layer 21 can be prevented from cracking. The thickness of the inorganic oxide layer 21 may be 6 nm or more, or 8 nm or more, or 100 nm or less, or 50 nm or less.
[0056] The inorganic oxide layer 21 can be formed by a normal vacuum deposition method. It can also be formed by other thin film formation methods such as sputtering, ion plating, plasma vapor deposition (CVD), etc. The inorganic oxide layer 21 may be formed by the vacuum deposition method from the viewpoint of excellent productivity.
[0057] The heating means for the vacuum deposition method may be any of the electron beam heating method, the resistance heating method, and the induction heating method. The vacuum deposition method may be the electron beam heating method from the viewpoint of a wide range of evaporation material selection. From the viewpoint of improving the adhesion between the multilayer polyethylene film 10 and the inorganic oxide layer 21 and the denseness of the inorganic oxide layer 21, deposition may be performed by a plasma assist method, an ion beam assist method, or the like. From the viewpoint of improving the transparency of the inorganic oxide layer 21, deposition may be performed by reactive deposition.
[0058] (Gas barrier coating layer) The gas barrier coating layer 22 is a layer provided for the purpose of protecting the inorganic oxide layer 21 and complementing the gas barrier property. The laminate 100 does not necessarily have to include the gas barrier coating layer 22.
[0059] The gas barrier coating layer 22 may contain a water-soluble polymer and at least one selected from the group consisting of a metal alkoxide, a hydrolysate thereof, and a reaction product thereof, or may contain at least one selected from the group consisting of a silane coupling agent, a hydrolysate thereof, and a reaction product thereof.
[0060] Examples of the water-soluble polymer include polyvinyl alcohol, polyvinylpyrrolidone, starch, methyl cellulose, carboxymethyl cellulose, sodium alginate, etc. The water-soluble polymer may be polyvinyl alcohol (PVA) from the viewpoint of excellent gas barrier properties.
[0061] Examples of metal alkoxides include compounds represented by the following general formula: M(OR 11 ) m (R 12 ) n-m …(1) In the above formula (1), R 11 and R 12 R is each independently a monovalent organic group having 1 to 8 carbon atoms. 11 and R 12 may each independently be an alkyl group such as a methyl group or an ethyl group. M represents an n-valent metal atom such as Si, Ti, Al, or Zr. m is an integer from 1 to n. 11 and R 12 If there are multiple, R 11 R 12 They may be the same or different.
[0062] Examples of the metal alkoxide include tetraethoxysilane [Si(OC2H5)4], triisopropoxyaluminum [Al(O-2'-C3H7)3], etc. The metal alkoxide may be tetraethoxysilane or triisopropoxyaluminum from the viewpoint of being relatively stable in an aqueous solvent after hydrolysis.
[0063] Examples of the silane coupling agent include compounds represented by the following general formula: Si(OR 21 ) p (R 22 ) 3-p R 23 …(2) In the above formula (2), R 21 represents an alkyl group such as a methyl group or an ethyl group, and R 22 represents a monovalent organic group such as an alkyl group, an aralkyl group, an aryl group, an alkenyl group, an alkyl group substituted with an acryloxy group, or an alkyl group substituted with a methacryloxy group, and R 23 represents a monovalent organic functional group, and p represents an integer of 1 to 3. 21 or R 22 If there are multiple, R 21 R 22 R may be the same or different. 23 Examples of the monovalent organic functional group represented by the formula (I) include a monovalent organic functional group containing a glycidyloxy group, an epoxy group, a mercapto group, a hydroxyl group, an amino group, an alkyl group substituted with a halogen atom, and an isocyanate group. The silane coupling agent may be a polymer such as a dimer or trimer of the above-mentioned silane coupling agent.
[0064] Examples of the silane coupling agent include vinyltrimethoxysilane, γ-chloropropylmethyldimethoxysilane, γ-chloropropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropylmethyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, and γ-methacryloxypropylmethyldimethoxysilane.
[0065] The gas barrier coating layer 22 can be formed by dissolving a water-soluble polymer in water or a water / alcohol mixed solvent, mixing it with a metal alkoxide, a silane coupling agent, or a hydrolyzate thereof to obtain a mixed solution, applying the mixed solution to the surface of the inorganic oxide layer 21, and drying by heating. Additives such as an isocyanate compound, a dispersant, a stabilizer, a viscosity adjuster, and a colorant may be added to the mixed solution.
[0066] When the water-soluble polymer is PVA, the content of PVA in the mixed solution may be 20 to 50 mass % or 25 to 40 mass % based on the total solid content of the mixed solution. When the content of PVA is 20 mass % or more, it becomes easy to form the gas barrier coating layer 22. When the content of PVA is 50 mass % or less, the gas barrier property is excellent.
[0067] The gas barrier coating layer 22 may be a coating containing a polyvalent metal salt of polycarboxylic acid, which is a reaction product between a carboxy group of a polycarboxylic acid polymer and a polyvalent metal compound (a polyvalent metal salt coating of polycarboxylic acid). The polyvalent metal salt coating of polycarboxylic acid can be formed by applying a mixed solution of a polycarboxylic acid polymer and a polyvalent metal compound to the surface of the inorganic oxide layer 21 and drying the mixture. Alternatively, a coating liquid mainly composed of a polycarboxylic acid polymer may be applied to the surface of the inorganic oxide layer 21 and dried to form a coating, and then a coating liquid mainly composed of a polyvalent metal compound may be applied to the coating and dried to form a coating, and a crosslinking reaction may be caused between these coatings to form the polyvalent metal salt coating of polycarboxylic acid.
[0068] The polycarboxylic acid polymer is a polymer having two or more carboxyl groups in the molecule. Examples of the polycarboxylic acid polymer include polymers of ethylenically unsaturated carboxylic acids, copolymers of ethylenically unsaturated carboxylic acids and other ethylenically unsaturated monomers, and acidic polysaccharides having carboxyl groups in the molecule, such as alginic acid, carboxymethylcellulose, and pectin.
[0069] Examples of the ethylenically unsaturated carboxylic acid include acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, etc. Examples of the ethylenically unsaturated monomer copolymerizable with the ethylenically unsaturated carboxylic acid include saturated carboxylic acid vinyl esters such as ethylene, propylene, and vinyl acetate, alkyl acrylates, alkyl methacrylates, alkyl itaconates, vinyl chloride, vinylidene chloride, styrene, acrylamide, and acrylonitrile, etc. The polycarboxylic acid polymer may be one type or two or more types.
[0070] From the viewpoint of excellent gas barrier properties, the ethylenically unsaturated carboxylic acid polymer is preferably a polymer containing a structural unit derived from at least one monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, itaconic acid, fumaric acid, and crotonic acid, and more preferably a polymer containing a structural unit derived from at least one monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, and itaconic acid.
[0071] In the ethylenically unsaturated carboxylic acid polymer, the proportion of structural units derived from at least one monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, and itaconic acid is preferably 80 mol % or more, and more preferably 90 mol % or more, based on the total amount of monomers in the polymer.
[0072] The number average molecular weight of the polycarboxylic acid polymer is preferably 2,000 to 10,000,000, and more preferably 5,000 to 1,000,000. When the number average molecular weight is 2,000 or more, the laminate has sufficient water resistance, and deterioration of gas barrier properties and transparency and whitening caused by moisture can be suppressed. When the number average molecular weight is 10,000,000 or less, the viscosity of the coating liquid when forming the gas barrier coating layer 22 does not become too high, and the coating can be easily formed.
[0073] In the case where a coating liquid mainly composed of a polycarboxylic acid polymer is applied and dried to form a coating, and then a coating liquid mainly composed of a polyvalent metal compound is formed, a part of the carboxyl groups of the polycarboxylic acid polymer may be neutralized in advance with a basic compound. By neutralizing a part of the carboxyl groups of the polycarboxylic acid polymer in advance, the water resistance and heat resistance can be further improved. The basic compound may be at least one basic compound selected from the group consisting of a polyvalent metal compound, a monovalent metal compound, and ammonia. Examples of the polyvalent metal compound include compounds exemplified as polyvalent metal compounds described later. Examples of the monovalent metal compound include sodium hydroxide, potassium hydroxide, and the like.
[0074] The coating liquid containing a polycarboxylic acid polymer as a main component may contain additives such as a crosslinking agent, a curing agent, a leveling agent, an antifoaming agent, an antiblocking agent, an antistatic agent, a dispersing agent, a surfactant, a softener, a stabilizer, a film-forming agent, and a thickener.
[0075] The solvent used in the coating liquid containing a polycarboxylic acid polymer as a main component is preferably an aqueous medium. Examples of the aqueous medium include water, water-soluble or hydrophilic organic solvents, and mixtures thereof. The aqueous medium contains water as a main component. The content of water in the aqueous medium may be 70% by mass or more, or 80% by mass or more. Examples of the water-soluble or hydrophilic organic solvent include alcohols such as methanol, ethanol, and isopropanol; ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran; nitriles such as acetonitrile; cellosolves, carbitols, and the like.
[0076] The polyvalent metal compound is not particularly limited as long as it is a compound that reacts with the carboxyl group of the polycarboxylic acid polymer to form a polyvalent metal salt of polycarboxylic acid, and examples thereof include zinc oxide, magnesium oxide, magnesium methoxide, copper oxide, calcium carbonate, etc. The polyvalent metal compound may be zinc oxide from the viewpoint of excellent gas barrier properties. One or more types of polyvalent metal compounds may be used.
[0077] Zinc oxide is an inorganic material having ultraviolet absorbing properties. When zinc oxide is in the form of particles, the average particle size of the zinc oxide particles may be 5 μm or less, 1 μm or less, or 0.1 μm or less, from the viewpoints of gas barrier properties, transparency, and formability of a coating film.
[0078] When a coating film is formed by applying and drying a coating liquid containing a polyvalent metal compound as a main component, the coating liquid may contain, in addition to the polyvalent metal compound (e.g., zinc oxide particles), a solvent, a resin that is soluble or dispersible in the solvent, a dispersant, a softener, a stabilizer, a film-forming agent, a thickener, etc.
[0079] Examples of resins that are soluble or dispersible in a solvent include alkyd resins, melamine resins, acrylic resins, urethane resins, polyester resins, phenolic resins, amino resins, fluororesins, epoxy resins, isocyanate resins, etc. When the coating liquid contains these resins, the coating properties and film-forming properties are improved.
[0080] As the dispersant, an anionic surfactant or a nonionic surfactant can be used. Examples of the surfactant include (poly)carboxylate, alkyl sulfate, alkylbenzene sulfonate, alkylnaphthalene sulfonate, alkyl sulfosuccinate, alkyldiphenyl ether disulfonate, alkyl phosphate, aromatic phosphate, polyoxyethylene alkyl ether, polyoxyethylene alkylphenol ether, polyoxyethylene alkyl ester, alkyl allyl sulfate, polyoxyethylene alkyl phosphate, sorbitan alkyl ester, glycerin fatty acid ester, sorbitan fatty acid ester, sucrose fatty acid ester, polyethylene glycol fatty acid ester, polyoxyethylene sorbitan alkyl ester, polyoxyethylene alkyl allyl ether, polyoxyethylene derivative, polyoxyethylene sorbitol fatty acid ester, polyoxy fatty acid ester, polyoxyethylene alkylamine, etc. These surfactants may be used alone or in combination.
[0081] When the coating liquid containing a polyvalent metal compound as a main component contains an additive, the mass ratio of the polyvalent metal compound to the additive (polyvalent metal compound:additive) may be 30:70 to 99:1, or 50:50 to 98:2.
[0082] Examples of the solvent used in the coating liquid containing a polyvalent metal compound as a main component include water, methyl alcohol, ethyl alcohol, isopropyl alcohol, n-propyl alcohol, n-butyl alcohol, n-pentyl alcohol, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, toluene, hexane, heptane, cyclohexane, acetone, methyl ethyl ketone, diethyl ether, dioxane, tetrahydrofuran, ethyl acetate, and butyl acetate. From the viewpoint of coating properties, the solvent may be at least one selected from the group consisting of methyl alcohol, ethyl alcohol, isopropyl alcohol, toluene, ethyl acetate, methyl ethyl ketone, and water, and from the viewpoint of film-forming properties, it may be at least one selected from the group consisting of methyl alcohol, ethyl alcohol, isopropyl alcohol, and water. One or more solvents may be used.
[0083] Examples of the method for applying the coating liquid include casting, dipping, roll coating, gravure coating, screen printing, reverse coating, spray coating, kit coating, die coating, metalling bar coating, chamber doctor combined coating, and curtain coating.
[0084] The gas barrier coating layer 22 described above can maintain excellent gas barrier properties even after heat sterilization. Therefore, when the laminate 100 is used as a packaging material for heat sterilization, the packaging material has excellent adhesion even after heat sterilization. In addition, the gas barrier coating layer 22 described above is preferable because it has sufficient transparency, bending resistance, and stretch resistance, and there is no risk of generating harmful substances such as dioxins.
[0085] The thickness of the gas barrier coating layer 22 may be 0.05 μm or more, or 0.1 μm or more, from the viewpoint of excellent gas barrier properties. The thickness of the gas barrier coating layer 22 may be 1 μm or less, or 0.5 μm or less, from the viewpoints of easily forming a uniform coating surface, reducing the load due to drying, and production costs.
[0086] (Anchor coat layer) From the viewpoint of improving the adhesion between the multilayer polyethylene film 10 and the gas barrier layer 20, an anchor coat layer (not shown) may be provided between the multilayer polyethylene film 10 and the gas barrier layer 20. By providing the anchor coat layer, it becomes easier to maintain the gas barrier properties and adhesion even after heat sterilization treatment.
[0087] The anchor coat layer can be formed, for example, from a coating liquid containing a resin such as an acrylic resin, an epoxy resin, an acrylic urethane resin, a polyester polyurethane resin, a polyether polyurethane resin, etc. From the viewpoint of heat resistance and interlayer adhesive strength, the anchor coat layer may be formed from a coating liquid containing an acrylic urethane resin or a polyester polyurethane resin.
[0088] The method for applying the coating liquid for forming the anchor coat layer may be a known coating method, and examples thereof include an immersion method (dipping method), a method using a spray, a coater, a printer, a brush, etc. Examples of the types of coaters and printers used in these methods and the coating methods thereof include gravure coaters such as direct gravure method, reverse gravure method, kiss reverse gravure method, and offset gravure method, reverse roll coaters, microgravure coaters, coaters combined with chamber doctor, air knife coaters, dip coaters, bar coaters, comma coaters, die coaters, etc.
[0089] The method for drying the anchor coat layer is not particularly limited, but examples thereof include a method of natural drying, a method of drying in an oven set at a predetermined temperature, and a method using a dryer attached to a coater, such as an arch dryer, a floating dryer, a drum dryer, an infrared dryer, etc. Drying conditions can be appropriately selected depending on the drying method, and for example, in a method of drying in an oven, drying may be performed at 60 to 100°C for about 1 second to 2 minutes.
[0090] The thickness of the anchor coat layer may be 0.01 μm or more, 0.03 μm or more, or 0.05 μm or more from the viewpoint of easily obtaining sufficient adhesion between layers. The thickness of the anchor coat layer may be 5 μm or less, 3 μm or less, or 2 μm or less from the viewpoint of excellent gas barrier property.
[0091] <Adhesive layer> The adhesive layer 30 is a layer containing at least one type of adhesive, and is provided between the gas barrier layer 20 and the sealant layer 40 to bond them together. The adhesive layer 30 can be formed using a known adhesive. The adhesive may be, for example, a dry lamination adhesive. The dry lamination adhesive is not particularly limited, and examples thereof include ester adhesives, ether adhesives, and urethane adhesives. These adhesives may be one-component curing types or two-component curing types.
[0092] From the viewpoint of excellent gas barrier properties, the adhesive layer 30 may be formed using a gas barrier adhesive. Even if minute cracks occur in the inorganic oxide layer 21 or the gas barrier coating layer 22, the gas barrier adhesive can fill in the cracks and fill them, so that the deterioration of the gas barrier properties of the laminate 100 can be suppressed.
[0093] Gas barrier adhesives are adhesives that can exhibit gas barrier properties after curing. Examples of gas barrier adhesives include epoxy adhesives and polyester / polyurethane adhesives. Specific examples of gas barrier adhesives include "Maxive" manufactured by Mitsubishi Gas Chemical Company, Inc. and "Paslim" manufactured by DIC Corporation.
[0094] The oxygen permeability of the gas barrier adhesive is, for example, 150 cc / m 2 ·day·atm or less is preferable, and 100cc / m 2 ·day·atm or less is more preferable, and 80cc / m 2 ·day·atm or less is more preferable, and 50cc / m 2 By having the oxygen permeability within the above range, the gas barrier properties of the laminate 100 can be sufficiently improved.
[0095] The adhesive layer 30 can be formed by, for example, applying an adhesive by a bar coating method, a dipping method, a roll coating method, a gravure coating method, a reverse coating method, an air knife coating method, a comma coating method, a die coating method, a screen printing method, a spray coating method, a gravure offset method, or the like to form a coating film, and then drying and curing the coating film. From the viewpoint of suppressing cracking of the inorganic oxide layer 21, the adhesive layer 30 is preferably formed directly on the surface of the inorganic oxide layer 21 or the gas barrier coating layer 22. That is, the adhesive layer 30 is preferably formed by applying an adhesive directly on the surface of the inorganic oxide layer 21 or the gas barrier coating layer 22, and drying and curing it.
[0096] The temperature for drying the coating film may be, for example, 30 to 200° C., and preferably 50 to 180° C. The temperature for curing the coating film may be, for example, 20 to 70° C., and preferably 30 to 60° C. By keeping the drying and curing temperatures within the above ranges, the occurrence of cracks in the inorganic oxide layer 21 and the adhesive layer 30 can be suppressed, and the gas barrier property of the laminate 100 can be sufficiently improved.
[0097] The thickness of the adhesive layer 30 is preferably 0.1 to 20 μm, more preferably 0.5 to 10 μm, and even more preferably 1 to 5 μm. When the thickness of the adhesive layer 30 is 0.1 μm or more, it is possible to obtain a cushioning property that absorbs external impacts, which makes it easier to suppress cracking of the inorganic oxide layer 21 and further improves the gas barrier property of the laminate 100. When the thickness of the adhesive layer is 20 μm or less, it is likely that the flexibility of the laminate 100 can be sufficiently maintained.
[0098] The thickness of the adhesive layer 30 is preferably 50 times or more the thickness of the inorganic oxide layer 21. By making the thickness of the adhesive layer 30 50 times or more the thickness of the inorganic oxide layer 21, it is possible to obtain a cushioning property that absorbs external impacts, so that it becomes easier to suppress cracking of the inorganic oxide layer 21, and the gas barrier property of the laminate 100 can be further improved. The thickness of the adhesive layer 30 is preferably 300 times or less the thickness of the inorganic oxide layer 21. By making the thickness of the adhesive layer 30 300 times or less the thickness of the inorganic oxide layer 21, the flexibility and processability of the laminate 100 are excellent, and the cost can be reduced.
[0099] <Sealant layer> The sealant layer 40 is, for example, a layer made of a polyethylene resin. The sealant layer 40 is a layer that is bonded by heat fusion (heat sealing) when the laminate 100 is used to form a packaging material such as a packaging bag. The polyethylene resin constituting the sealant layer 40 may be a low-density polyethylene resin (LDPE), a linear low-density polyethylene resin (LLDPE), or a very low-density polyethylene resin (VLDPE) from the viewpoint of excellent heat sealing properties. From the viewpoint of environmental load, the sealant layer 40 may be made of a polyethylene resin derived from biomass or a recycled polyethylene resin. The sealant layer 40 may be, for example, made of a non-oriented polyethylene film.
[0100] Low density polyethylene has a density of 0.900 g / cm 3 More than 0.925g / cm 3 For linear low density polyethylene, polyethylene having a density of 0.900 g / cm3 or less can be used. 3 More than 0.925g / cm 3 For ultra-low density polyethylene, polyethylene with a density of 0.900 g / cm3 can be used. 3 Less than 100 mm of polyethylene can be used.
[0101] The sealant layer 40 may contain a resin other than polyethylene resin. Examples of resins other than polyethylene resin include olefin-based resins such as ethylene-vinyl acetate copolymer (EVA), ethylene-α-olefin copolymer, ethylene-(meth)acrylic acid copolymer, homopolypropylene resin (PP), propylene-ethylene random copolymer, propylene-ethylene block copolymer, propylene-α-olefin copolymer, and polybutene. The sealant layer 40 may contain additives such as antioxidants, lubricants, antiblocking agents, and antistatic agents.
[0102] The thickness of the sealant layer 40 may be, for example, 20 μm or more, 40 μm or more, or 50 μm or more. When the thickness of the sealant layer 40 is 20 μm or more, sufficient heat seal strength can be achieved. The thickness of the sealant layer 40 may be, for example, 200 μm or less, 170 μm or less, or 150 μm or less. When the thickness of the sealant layer 40 is 200 μm or less, excellent processability is achieved.
[0103] As shown in FIG. 4, the laminate 400 may include a second adhesive layer 70 on the surface opposite to the sealant layer 40 of the multilayer polyethylene film 10, and a substrate 80 disposed via the second adhesive layer 70.
[0104] <Second Adhesive Layer> The second adhesive layer 70 is a layer containing at least one type of adhesive, and is provided between the multilayer polyethylene film 10 and the substrate 80 to bond them together. The adhesive used for the second adhesive layer 70 may be a one-component curing adhesive or a two-component curing adhesive. Examples of the adhesive include a urethane adhesive, an epoxy adhesive, and a silicone adhesive. The second adhesive layer may be the adhesive used to form the adhesive layer 30 described above.
[0105] The thickness of the second adhesive layer 70 may be, for example, 0.5 μm or more, 0.8 μm or more, or 1 μm or more, and may be 6 μm or less, 5 μm or less, or 4.5 μm or less.
[0106] <Base material> The substrate 80 is the outermost layer of the laminate 400, and is a layer provided for the purpose of protecting the laminate 400. The substrate 80 may be, for example, a layer containing a polyethylene resin, or may be a polyethylene film. The substrate 80 may contain additives such as an antioxidant, a lubricant, an antiblocking agent, and an antistatic agent in addition to the polyethylene resin.
[0107] The difference in heat fusion temperature between the substrate 80 and the sealant layer 40 may be 10° C. or more. When the difference in heat fusion temperature between the substrate 80 and the sealant layer 40 is 10° C. or more, a packaging bag can be easily formed when the packaging bag is produced using the laminate 400 as a packaging material.
[0108] The thickness of the substrate 80 may be, for example, 10 μm or more, 20 μm or more, or 30 μm or more, and may be 200 μm or less, 150 μm or less, or 100 μm or less.
[0109] The laminate 100 may further include a printed layer (not shown). The printed layer is provided at a position visible from the outside of the laminate 100 for the purpose of displaying information about the contents, identifying the contents, or improving the design of the packaging bag. The printed layer may be provided, for example, on the surface of the inorganic oxide layer 21, the surface of the gas barrier coating layer 22, or the surface of the sealant layer 40 of the laminate 100.
[0110] The method for forming the printed layer is not particularly limited, and known printing methods and printing inks can be used. The printing method and printing ink are appropriately selected in consideration of, for example, printability for each layer of the laminate 100, design such as color tone, adhesion, and safety as a food container.
[0111] Examples of printing methods include gravure printing, offset printing, gravure offset printing, flexographic printing, and inkjet printing. Among these, gravure printing is preferred from the viewpoints of productivity and high definition of the image.
[0112] In order to improve the adhesion of the printed layer, the surface of the layer forming the printed layer may be subjected to pretreatment such as corona treatment, plasma treatment, frame treatment, etc., or a coating layer such as an easy-adhesion layer may be provided.
[0113] <Packaging materials> The laminate 100 can be used as a packaging material for forming packaging bags, etc. Specifically, it can be used as a packaging material for flat bags, three-sided bags, palm-shaped bags, gusseted bags, standing pouches, pouches with spouts, pouches with beaks, etc.
[0114] The laminate 100 can be used as a packaging material as well as a film for electronic devices, a film for solar cells, a film for fuel cells, a substrate film, and the like. EXAMPLES
[0115] The present invention will be described in detail below with reference to examples, although the present invention is not limited to the following examples.
[0116] <Polyethylene resin> ·Resin A: Density 0.950g / cm 3 , MFR1.1g / 10min. ·Resin B: Density 0.958g / cm 3 , MFR1g / 10min. ·Resin C: Density 0.949g / cm 3 , MFR 0.3g / 10min. ·Resin D: Density 0.960g / cm 3 , MFR1g / 10min. ·Resin E: Density 0.944g / cm 3 , MFR 0.45g / 10min. ·Resin F: Density 0.926g / cm 3 , MFR 0.85g / 10min. ·Resin G: Density 0.941g / cm 3 , MFR1.3g / 10min. ·Resin H: Density 0.962g / cm 3 , MFR 0.85g / 10min. ·Resin I: Density 0.920g / cm 3 , MFR 0.85g / 10min.
[0117] <Preparation of polyethylene film> (Examples 1 to 20, Comparative Examples 1 to 8) The resins shown in Tables 1 to 6 constituting the surface layer, intermediate layer, and back layer were respectively fed into an extruder and melt-kneaded at 190°C, after which polyethylene resin was introduced through a three-layer die and a multilayer polyethylene film was produced by an air-cooled inflation method. The overall thickness of the multilayer polyethylene films produced in each Example and Comparative Example was within the range of 25 to 40 μm. The polyethylene resin content of the multilayer polyethylene films produced in each Example and Comparative Example was 90 mass% or more.
[0118] Example 21 The resins shown in Table 6 constituting Layers 1 to 5 were each fed into an extruder and melt-kneaded at 190°C, after which polyethylene resin was introduced through a 5-layer die and an air-cooled inflation method was used to produce a multilayer polyethylene film in which Layers 1 and 2 were surface layers, Layer 3 was an intermediate layer, and Layers 4 and 5 were back layers. The polyethylene resin content of each of the produced multilayer polyethylene films was 90 mass% or more.
[0119] Example 22 The resins shown in Table 6 constituting Layers 1 to 7 were each fed into an extruder and melt-kneaded at 190°C, after which polyethylene resin was introduced through a 7-layer die and an air-cooled inflation method was used to produce a multilayer polyethylene film in which Layers 1 and 2 were surface layers, Layers 3 to 5 were middle layers, and Layers 6 and 7 were back layers. The polyethylene resin content of each of the produced multilayer polyethylene films was 90 mass% or more.
[0120] (Example 23) The resins shown in Table 6 constituting Layers 1 to 7 were each fed into an extruder and melt-kneaded at 190°C, after which polyethylene resin was introduced through a 7-layer die and an air-cooled inflation method was used to produce a multilayer polyethylene film in which Layer 1 was the surface layer, Layers 2 to 6 were the middle layers, and Layer 7 was the back layer. The polyethylene resin content of each of the produced multilayer polyethylene films was 90 mass% or more.
[0121] Example 24 The resins shown in Table 6 constituting Layers 1 to 7 were each fed into an extruder and melt-kneaded at 190°C, after which polyethylene resin was introduced through a 7-layer die and an air-cooled inflation method was used to produce a multilayer polyethylene film in which Layers 1 and 2 were surface layers, Layers 3 to 5 were middle layers, and Layers 6 and 7 were back layers. The polyethylene resin content of each of the produced multilayer polyethylene films was 90 mass% or more.
[0122] <Tip drop temperature> The probe drop temperature (softening point) of each layer of the multilayer polyethylene film was measured using an atomic force microscope equipped with a nanothermal microscope consisting of a cantilever (probe) with a heating mechanism. First, the multilayer polyethylene film was embedded in a visible light curing resin to obtain a measurement sample. Next, in a -140°C environment, the measurement sample was cross-cut in a direction parallel to the TD direction using a diamond knife of a cryo-ultramicrotome. After measuring the thickness of each layer from the cross section of the multilayer polyethylene film, the probe drop temperature of the multilayer polyethylene film was measured as follows.
[0123] The atomic force microscope used was an MPF-3D-SA manufactured by Oxford Instruments, the nanothermal microscope equipped with the atomic force microscope was a Ztherm manufactured by Oxford Instruments, and the cantilever was an AN2-200 (trade name) manufactured by Anasys Instruments. After measuring the shape of the sample with a 10 μm field of view in AC mode, the cantilever was separated from the sample by 5 to 10 μm in the Z direction (normal direction of the sample surface). In this state, the detrend correction function of the device was performed in contact mode under conditions of a maximum applied voltage of 6 V and a heating rate of 0.5 V / s to correct the change in the deflection of the cantilever due to the application of voltage. After that, the cantilever was brought into contact with the sample in contact mode so that the change in deflection before and after the contact between the cantilever and the sample was 0.2 V, and the sample was heated by applying a voltage to the cantilever under conditions of a maximum applied voltage of 6 V and a heating rate of 0.5 V / s while maintaining a constant deflection value. The displacement of the cantilever in the Z direction at this time was recorded, and the measurement was stopped when the Z displacement changed from rising to falling and fell 50 nm from the change point. If the Z displacement did not fall 50 nm from the change point and reached the maximum applied voltage, the maximum applied voltage during detrend correction and measurement was increased by 0.5 V and the measurement was repeated. The applied voltage at which the recorded Z displacement was maximum was converted into temperature. This measurement was performed at 10 points within a 10 μm field of view, and the average value of the 10 points was taken as the probe drop temperature. The probe drop temperatures for each layer of the multilayer polyethylene film are shown in Tables 1 to 6.
[0124] A calibration curve was used to convert the applied voltage to temperature. Polycaprolactone (melting point 60°C), low-density polyethylene (melting point 112°C), polypropylene (melting point 166°C), and polyethylene terephthalate (melting point 255°C) were measured as calibration samples, and a calibration curve of applied voltage and temperature was created. Here, the melting point was the melting peak temperature measured by a differential scanning calorimeter (DSC) at a heating rate of 5°C / min. The measurement method for the calibration samples was the same as that for the samples, but the maximum applied voltage during Detrend correction and measurement was set to 3.5 V if the sample was polycaprolactone, 5.5 V if the sample was low-density polyethylene, 6.5 V if the sample was polypropylene, and 7.8 V if the sample was polyethylene terephthalate. The relationship between the applied voltage at which the Z displacement was maximum when measuring each calibration sample was approximated by a cubic function using the least squares method to create a calibration curve, and the calibration curve was obtained.
[0125] <Preparation of Laminate> The surface of the outer layer side of the multilayer polyethylene films produced in Examples 1 to 20 and Comparative Examples 1 to 8 was subjected to a corona treatment. Next, an anchor coat layer, an inorganic oxide layer, a gas barrier coating layer, an adhesive layer, and a sealant layer were formed on the surface of the multilayer polyethylene film by the method described below so as to have the configurations shown in Tables 1 to 5, and the multilayer polyethylene film / anchor coat layer / inorganic oxide layer / gas barrier coating layer / adhesive layer / sealant layer were laminated in this order, and then aged at 40° C. for 4 days to obtain a laminate. The polyethylene resin content in the laminates produced in each Example and Comparative Example was 90% by mass or more.
[0126] The surface of the back layer side of the multilayer polyethylene films produced in Examples 21 to 24 was corona-treated. Next, an anchor coat layer, an inorganic oxide layer, a gas barrier coating layer, an adhesive layer, and a sealant layer were formed on the surface of the multilayer polyethylene film by the method described below so as to have the configuration shown in Table 6. Next, "LA7735" (a polyisocyanate component) manufactured by Henkel Japan Co., Ltd. and "LA6159" (a polyol component) manufactured by Henkel Japan Co., Ltd. were mixed in a two-liquid mixing and supplying device in a mass ratio of 100:45 to obtain a two-liquid curing urethane adhesive. The urethane adhesive was applied in a solventless adhesive laminator at a processing speed of 100 m / min, doctor roll and coating roll temperatures of 60°C, and the adhesive was applied in an amount of 2.1 g / m2. 2 The adhesive layer was coated on the surface opposite to the sealant layer of the multilayer polyethylene film so that the adhesive layer was 90% by mass or more. Next, unstretched polyethylene (HDPE film, product name: HS31, manufactured by Tamapoly) was attached to the coated adhesive layer, and aged at 40°C for one day to obtain a laminate. The polyethylene resin content in the laminates produced in each of the Examples and Comparative Examples was 90% by mass or more.
[0127] <Anchor coat layer> Acrylic polyol and tolylene diisocyanate were mixed so that the number of NCO groups of tolylene diisocyanate was equal to the number of OH groups of the acrylic polyol, and diluted with ethyl acetate so that the total solid content (total amount of acrylic polyol and tolylene diisocyanate) was 5 mass%. β-(3,4 epoxycyclohexyl)trimethoxysilane was added to the diluted mixed liquid so that it was 5 parts by mass with respect to 100 parts by mass of the total amount of acrylic polyol and tolylene diisocyanate, and these were mixed to prepare a composition for forming an anchor coat layer (anchor coating agent). The anchor coat layer was formed by applying the composition for forming an anchor coat layer to the surface of a corona-treated multilayer polyethylene film by gravure coating and drying. The coating amount of polyester resin of the anchor coat layer was 0.1 g / m 2 It was.
[0128] <Inorganic oxide layer> When the inorganic oxide was silicon oxide, a transparent inorganic oxide layer made of silicon oxide and having a thickness of 30 nm was formed by a vacuum deposition apparatus using an electron beam heating method. When the inorganic oxide was aluminum oxide, a transparent inorganic oxide layer made of aluminum oxide and having a thickness of 15 nm was formed by a vacuum deposition apparatus using an electron beam heating method.
[0129] <Gas barrier coating layer> A gas barrier coating agent was prepared by mixing the following liquids A, B, and C in a mass ratio of 70 / 20 / 10, respectively. The gas barrier coating agent was applied by gravure coating and dried to form a gas barrier coating layer with a thickness of 0.3 μm. Liquid A: A hydrolyzed solution with a solid content of 5 mass% (SiO2 equivalent) obtained by adding 17.9 g of tetraethoxysilane (Si(OC2H5)4), 10 g of methanol, and 72.1 g of 0.1N hydrochloric acid and stirring for 30 minutes. Liquid B: A mixed solution of 5% polyvinyl alcohol, water, and methanol in a mass ratio of 95:5. Liquid C: A hydrolysis solution in which 1,3,5-tris(3-trialkoxysilylpropyl)isocyanurate was diluted with a mixed solution of water / isopropyl alcohol (water:isopropyl alcohol mass ratio 1:1) to a solid content of 5 mass%.
[0130] <Adhesive layer> Either of the following urethane-based adhesives or gas barrier adhesives was applied by dry lamination and dried to form an adhesive layer having a thickness of 3 μm. (Urethane adhesive) A urethane adhesive was obtained by mixing 100 parts by mass of Takelac A525 (manufactured by Mitsui Chemicals), 11 parts by mass of Takenate A52 (manufactured by Mitsui Chemicals), and 84 parts by mass of ethyl acetate.
[0131] (Gas barrier adhesive) A gas barrier adhesive was obtained by mixing 23 parts by mass of a solvent made by mixing ethyl acetate and methanol in a mass ratio of 1:1 with 16 parts by mass of Maxive C93T (manufactured by Mitsubishi Gas Chemical Co., Ltd.) and 5 parts by mass of Maxive M-100 (manufactured by Mitsubishi Gas Chemical Co., Ltd.).
[0132] <Sealant layer> As the sealant layer, a 60 μm-thick unstretched film made of linear low-density polyethylene resin (LLDPE) (manufactured by Mitsui Chemicals Tocello, product name: TUX-MCS) was used.
[0133] <Molecular orientation degree> The degree of molecular orientation of the molecular chains in the plane of the multilayer polyethylene film was measured by rotating the multilayer polyethylene film in a microwave polarized electric field using a microwave molecular orientation meter (Oji Measurement Instruments Co., Ltd., product name MOA-5012A). The measurement results are shown in Tables 1 to 6.
[0134] [evaluation] <Processing stability> The multilayer polyethylene film after the gas barrier layer was formed was visually inspected and the processing stability was evaluated based on the following evaluation criteria. The evaluation results are shown in Tables 1 to 6. A: No wrinkles were observed in the appearance or rolled state of the multilayer polyethylene film. B: Slight wrinkles were observed in either the appearance or rolled state of the multilayer polyethylene film. C: Numerous wrinkles were observed in either the appearance or rolled state of the multilayer polyethylene film.
[0135] <Gas barrier properties> The laminates produced in each of the Examples and Comparative Examples were measured for oxygen permeability (cm) using an oxygen permeability measuring device (product name OXTRAN-2 / 20, manufactured by MOCON) under an atmosphere of 30°C and 70% RH. 3 / (m 2 The gas barrier properties were evaluated based on the following criteria. The evaluation results are shown in Tables 1 to 6. A+: Oxygen permeability is 2cm 3 / (m 2·day·atm). A: Oxygen permeability is 2cm 3 / (m 2 ·day · atm) or more, 5cm 3 / (m 2 ·day·atm). A-: Oxygen permeability is 5cm 3 / (m 2 ·day · atm) or more, 10cm 3 / (m 2 ·day·atm). B+: Oxygen permeability is 10cm 3 / (m 2 ·day · atm) or more, 20cm 3 / (m 2 ·day·atm). B: Oxygen permeability is 20cm 3 / (m 2 ·day · atm) or more, 50cm 3 / (m 2 ·day·atm). B-: Oxygen permeability is 50cm 3 / (m 2 ·day · atm) or more, 100cm 3 / (m 2 ·day·atm). C: Oxygen permeability is 100cm 3 / (m 2 ·day·atm) or more.
[0136] <Gas barrier properties after boiling treatment> The laminate produced in each Example and Comparative Example was cut into two pieces with a size of 15 cm x 10 cm, and the two cut-out laminates were stacked so that the sealant layers faced each other, and three sides were impulse sealed to form a pouch. 150 ml of water was placed in the pouch as the content, and the remaining side was impulse sealed to produce a pouch (packaging bag) with four sides sealed. The produced pouch was boiled at 95°C for 30 minutes in a boiling treatment device. After the boiling treatment, the pouch was opened to remove the contents, and thoroughly dried, and the oxygen permeability of the pouch after the boiling treatment was measured by the above-mentioned method to evaluate the gas barrier property. The evaluation results are shown in Tables 1 to 6.
[0137] <Gas barrier properties after bending> The laminates prepared in each of the examples and comparative examples were cut into a size of 295 mm length x 210 mm width to prepare samples for evaluation. The samples for evaluation were attached to the fixed head of a Gelbo Flex Tester (manufactured by Tester Sangyo Co., Ltd., product name: BE-1005) in a cylindrical shape of 87.5 mm diameter x 210 mm. Both ends of the samples for evaluation were held with an initial gripping distance of 175 mm, and a twist of 440 degrees was applied with a stroke of 87.5 mm. This operation was repeated 10 times at a speed of 40 times / min to bend the samples for evaluation. Next, the oxygen permeability of the samples for evaluation after bending was measured by the above-mentioned method, and the gas barrier properties were evaluated. The evaluation results are shown in Tables 1 to 6.
[0138] <Adhesion> A 15 mm wide rectangular test piece was cut out from the laminate produced in each Example and Comparative Example, and the laminate strength between the multilayer polyethylene film and the heat seal layer was measured using an Orientec Tensilon universal testing machine RTC-1250 in accordance with JIS Z1707. The laminate strength was measured by T-peel in normal condition. The evaluation results are shown in Tables 1 to 6.
[0139] <Adhesion after boiling treatment> The laminate produced in each Example and Comparative Example was cut into two pieces with a size of 15 cm x 10 cm, and the two cut-out laminates were stacked so that the sealant layers of each laminate faced each other, and three sides were impulse sealed to form a pouch. 200 ml of water was placed in the pouch as the content, and the remaining side was impulse sealed to produce a pouch (packaging bag) with four sides sealed. The produced pouch was boiled at 95°C for 30 minutes in a boiling treatment device. After the boiling treatment, the pouch was opened to remove the contents, and after sufficient drying, a strip-shaped test piece with a width of 15 mm was cut out from the pouch. The laminate strength between the multilayer polyethylene film and the heat seal layer was measured using Orientec's Tensilon universal testing machine RTC-1250 in accordance with JIS Z1707. The laminate strength was measured by T-peel and normal conditions. The evaluation results are shown in Tables 1 to 6.
[0140] [Table 1]
[0141] [Table 2]
[0142] [Table 3]
[0143] [Table 4]
[0144] [Table 5]
[0145] [Table 6] [Explanation of symbols]
[0146] 10, 50, 60...multilayer polyethylene film, 11, 51, 61...surface layer, 12, 52, 62...intermediate layer, 13, 53, 63...back layer, 20...gas barrier layer, 21...inorganic oxide layer, 22...gas barrier coating layer, 30...adhesive layer, 40...sealant layer, 70...second adhesive layer, 80...substrate, 100, 200, 300, 400...laminate.
Claims
1. A laminate comprising a multilayer polyethylene film, an inorganic oxide layer, an adhesive layer, and a sealant layer, The multilayer polyethylene film has at least three layers, a surface layer, an intermediate layer, and a back layer, in this order on the sealant layer side; the probe drop temperature of the intermediate layer is higher than the probe drop temperature of the surface layer and is equal to or higher than the probe drop temperature of the back layer; The surface layer has a thickness of 0.926 g / cm 3 It is made of medium density polyethylene resin or high density polyethylene resin having a density of or above, A laminate, wherein the content of the polyethylene resin in the laminate is 90 mass% or more based on the total amount of the laminate.
2. The density of the multilayer polyethylene film is 0.942 g / cm 3 The laminate according to claim 1 .
3. The laminate according to claim 1 , wherein the intermediate layer has a probe drop temperature of 125° C. or higher.
4. 2. The laminate of claim 1, wherein the thickness of said intermediate layer is 33% or greater than the thickness of said multilayer polyethylene film.
5. 2. The laminate according to claim 1, wherein the absolute value of the degree of molecular orientation of the multilayer polyethylene film is less than 1.
07.
6. The laminate according to claim 1 , further comprising a gas barrier coating layer on a surface of the inorganic oxide layer on the side of the sealant layer.
7. The laminate of claim 1 , wherein the adhesive layer comprises a gas barrier adhesive.
8. a second adhesive layer disposed on the back surface of the multilayer polyethylene film; The laminate according to claim 1 , further comprising a substrate disposed via the second adhesive layer.
9. A packaging material comprising the laminate according to any one of claims 1 to 8.
Citation Information
Patent Citations
Aluminum vapor deposited polyethylene film and method of manufacturing the same
JP2001179878A
Film, laminate film and package composed of laminate film
JP2018024213A